Comprehensible input as a learning strategy for listening comprehension - Bernabe Suarez, David Ricardo (2024)
Listening comprehension is one of the most affected skills due to the techniques used in the classroom. The main resource that teachers use to carry out listening activities are audios, but the problem is that the audios are not of interest to the students, in addition, the students cannot understand the main message of the audios, consequently, students lose interest in continuing to practice the English language. The solution is not to learn the English language, the solution is to "acquire" the English language, that is why this research project called "Comprehensible Input as a learning strategy for listening comprehension", had as a general objective to identify the influence of the Input Understandable in the development of listening comprehension in students. The English language is essential in our society, it is important to find the most effective resources and techniques for students to acquire this language naturally, in this way students will learn new vocabulary in an entertaining way. For this research project, the qualitative and phenomenological research type method was applied. This research work had fifteen students from the "Unidad Educativa Muey" as a sample. An interview was applied to each one of them to know the opinion of the students about some resources and techniques based on the Comprehensible Input, such as songs and their lyrics, movies and television series, and the interpretation of words, and how these resources can influence them. At the end of this research project, it can be concluded that Comprehensible Input is positively accepted as a learning strategy, and it is interesting and entertaining for students to develop listening comprehension.